H i absorption at z ∼ 0.7 against the lobe of the powerful radio galaxy PKS 0409−75. Issue 2 (25th October 2021) - Mahony, Elizabeth K; Allison, James R; Sadler, Elaine M; Ellison, Sara L; Mao, Sui Ann; Morganti, Raffaella; Moss, Vanessa A; Seta, Amit; Tadhunter, Clive N; Weng, Simon; Whiting, Matthew T; Yoon, Hyein; et al.
ABSTRACT: We present results from a search for the H i 21-cm line in absorption towards 16 bright radio sources with the six-antenna commissioning array of the Australian Square Kilometre Array Pathfinder. Our targets were selected from the 2-Jy sample, a flux-limited survey of the southern radio sky with extensive multiwavelength follow-up. Two sources were detected in H i absorption including a new detection towards the bright Fanaroff–Riley Type II radio galaxy PKS 0409−75 at a redshift of z = 0.674. The H i absorption line is blueshifted by ∼3300 km s −1 compared to the optical redshift of the host galaxy of PKS 0409−75 at z = 0.693. Deep optical imaging and spectroscopic follow-up with the GMOS instrument on the Gemini-South telescope reveal that the H i absorption is associated with a galaxy in front of the southern radio lobe with a stellar mass of 3.2–6.8 × 10 11 M⊙, a star formation rate of ∼1.24 M⊙ yr −1, and an estimated H i column density of 2.16 × 10 21 cm −2, assuming a spin temperature of T spin = 500 K and source covering factor of C f = 0.3. Using polarization measurements of PKS 0409−75 from the literature, we estimate the magnetic field of the absorbing galaxy to be ∼14.5 μ G, consistent with field strengths observed in nearby spiral galaxies but larger than expected for an elliptical galaxy. Results from this pilot study can inform future surveys as new wide-field telescopes allow us to search for 21-cm H i absorption towards all bright radio sources as opposed to smaller targeted samples.